Implementation Of Dynamic Role-Based Access Control and Record Log-In Dependency Injection Based VRMS System - Paradhita, Astrid Noviana; Khadija, Mutiara Auliya; Purbayu, Agus; Bawono, Sahirul Alim Tri; Aziz, Abdul; Haryati, Sri; Daaniis Raditya Pramoda Wardani; Rafael Kurniawan Albyseptra Pratama (Program Studi Pendidikan Teknologi Infromasi UMK, 2024)
Human resource management is one of the critical factors for a company in order to realize the company's vision, mission, and goals. This requires effective and efficient human resource management by integrating the entire management process well. This is to manage the company's internal and external human resources. VRMS is an integrated application that can manage the company's external resources. VRMS is built based on dependency injection. VRMS has two superior features: role-based access control (RBCA) and record log. RBCA is a feature that manages all resources involved in a company project. At the same time, the record log allows super admins to monitor and evaluate the performance of all external company resources. The VRMS system is built using hybrid methodoly in software development life cycles from initiation phase, planning, execution, and testing. The testing process used in this system is the user acceptance test (UAT) method. The test results show that all features on VRMS can run 80% well.